2019
DOI: 10.3390/su12010200
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Different Transport Governance Strategies on Climate Change

Abstract: The transport industry is one of the few sectors in which emissions continue to grow, contributing 26% to the global CO2 emissions. Transport agencies everywhere in the world are focusing on mitigation strategies to reduce greenhouse gas emissions. Policy-makers are under pressure to tackle the issue of climate change and approach sustainable transport by promoting more sustainable practices and altering behavior. This paper attempts to explore the impact of transport on climate change through the lens of gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The environmental impacts of food distribution systems are primarily related to the transportation of goods. Improving the eco-efficiency in transport, currently estimated at around 15% of global greenhouse gas (GHG) emissions [1], represents one of the major challenges of the modern World [2][3][4], becoming one of the goals of the EU climate and energy policy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental impacts of food distribution systems are primarily related to the transportation of goods. Improving the eco-efficiency in transport, currently estimated at around 15% of global greenhouse gas (GHG) emissions [1], represents one of the major challenges of the modern World [2][3][4], becoming one of the goals of the EU climate and energy policy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The unfavorable effects of transport are noticed by both the environment and society. These effects, named external transport costs, differ depending on the level of economic development, the degree of advancement and utilization of various transport sectors (different transport branches), geographical location (including climate), as well as the susceptibility of environment elements (including fauna and flora) [81][82][83]. Pollution emitted to the environment by transport may spread far beyond the transport network.…”
Section: Multimodal Transport Within the International Spacementioning
confidence: 99%
“…Previous studies [48] revealed different socio-demographic factors such as race, age, education level, and significant income have a relationship with awareness of using public transport on using public transportations. These factors control variables that significantly affect the usage behavior of public transportation via behavioral intention [49,50], which suggests the behavior of the individual in terms of how they are going to use the public transport.…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%